La ausencia de corresponsabilidad familiar en jóvenes adultos - Bermeo Mendieta, Isis Romina; Naula Valarezo, Jennifer Noelia (Machala: Universidad Técnica de Machala, 2022)
This research focused on analyzing the psychological effects arising from the absence of family co-responsibility in young adults, variable that is defined as the inequitable distribution of domestic tasks in the home due to the lack of father figures. In most cases, this responsibility is assigned to external relatives such as grandparents or uncles, however, since these are not present, it is attributed directly to the firstborn son. As a frame of reference, the Systemic Family Theory was used, whose principle implies identifying the symptomatic behaviors presented in one or more members of the household, since this fact will affect in a circular way if it is not treated correctly, therefore, the objective of this current is based on improving the quality of life and functioning of the family. The factors of absence of parents were considered for its evaluation, the first impact, emotions and feelings manifested by the absence of family co-responsibility, psychological resources and personal aspirations that young adults establish in this situation. The study was held under the qualitative research approach of phenomenological-hermeneutic design, non-probabilistic-homogeneous sample, and 3 cases of women, the participants were selected by age range of 18 to 25 years, and have had under their responsibility the management and family organization during their adolescence until the current age, due to paternal absence. For data collection, the following were used, application of semi-structured qualitative interview, qualitative observation necessary to verify with the reports presented during the collection of information, active participation of the researcher and audiovisual tools useful for the analysis of the study. The results revealed that in these young people negative emotions and feelings arise, such as, sadness, loneliness, guilt, feeling of abandonment, frustration, resentment, anger, anger, anguish, among others, however, there are reduced positive feelings such as satisfaction, pride and strength, in turn, a series of psychological resources were evidenced, among which are, autonomy, hope, perseverance, and resilience, which they develop as a coping mechanism in the face of experiences raised from an early age at home, They also allow them to draw personal aspirations, with the family, social, work and with themselves. It is concluded that young adults with absence of family co-responsibility maintain physical exhaustion, despite this, emotional overload strongly commits them to the responsibility of the home, so the psychological area is mainly affected due to the obligations and constant demands they go through in their daily lives, along with the pressure to fulfill their role because there is no external help, giving them the feeling of not having the life they want or that is appropriate for their age compared to their peers, seeing this situation as a sacrifice for themselves; In addition, in their future projects they are not individualized in their entirety, that is, in their approaches to expectations they place themselves in the background, since the greatest purpose and motivation in their life is focused on ensuring the well-being and happiness of their family, providing personal satisfaction.
Esta investigación se centró en analizar los efectos psicológicos que surgen de la ausencia de corresponsabilidad familiar en los jóvenes adultos, variable que es definida como la distribución no equitativa de tareas domésticas en el hogar ante la falta de figuras paternas. En la mayoría de casos, esta responsabilidad es asignada a familiares externos como abuelos o tíos, no obstante, al no estar presentes éstos, se le atribuye directamente al hijo primogénito. Como marco de referencia se empleó la Teoría Familiar Sistémica, cuyo principio implica identificar las conductas sintomáticas presentadas en uno o más miembros del hogar, puesto que este hecho afectará de manera circular si no se trata correctamente, por ende, el objetivo de esta corriente se basa en mejorar la calidad de vida y funcionamiento de la familia. Se consideró para su evaluación los factores de ausencia de padres, el primer impacto, emociones y sentimientos manifestados por la ausencia de corresponsabilidad familiar, recursos psicológicos y aspiraciones personales que se establecen los jóvenes adultos en dicha situación. El estudio se sostuvo bajo el enfoque de investigación cualitativo de diseño fenomenológico-hermenéutico, muestra no probabilística-homogénea, y 3 casos de mujeres, las participantes fueron seleccionadas por rango de edad de 18 a 25 años, y haber tenido bajo su responsabilidad el manejo y organización familiar durante su adolescencia hasta la edad actual, debido a la ausencia paterna. Para la recolección de datos se utilizó, aplicación de entrevista cualitativa semiestructurada, observación cualitativa necesaria para constatar con los relatos expuestos durante la recopilación de información, participación activa del investigador y herramientas audiovisuales útiles para el análisis del estudio. Los resultados revelaron que en estos jóvenes surgen emociones y sentimientos negativos, tales como, tristeza, soledad, culpa, sentimiento de abandono, frustración, resentimiento, enojo, rabia, angustia, entre otros, sin embargo, existen reducidos sentimientos positivos como satisfacción, orgullo y fortaleza, a su vez, se evidenciaron una serie de recursos psicológicos, entre los cuales se encuentra, autonomía, esperanza, perseverancia, y resiliencia, que desarrollan como mecanismo de afrontamiento ante las experiencias suscitadas desde temprana edad en el hogar, también, les permiten trazarse aspiraciones personales, con la familia, sociales, laborales y consigo mismo. Se concluye que los jóvenes adultos con ausencia de corresponsabilidad familiar mantienen agotamiento físico, a pesar de ello, la sobrecarga emocional los compromete fuertemente con la responsabilidad del hogar, por lo que se ve afectada principalmente el área psicológica debido a las obligaciones y demandas constantes por las que atraviesan en su diario vivir, junto con la presión de cumplir su rol por no existir una ayuda externa, dándoles la sensación de no tener la vida que desean o que esté acorde para su edad en comparación a sus semejantes, viendo esta situación como un sacrificio para sí, además, en sus proyectos a futuro no se individualizan en su totalidad, es decir, que en sus planteamientos de expectativas se colocan a sí mismos en segundo plano, ya que el mayor propósito y motivación en su vida se centra en velar por el bienestar y felicidad de su familia, aportando satisfacción personal.
Keywords: CORRESPONSABILIDAD FAMILIAR; RECURSO PSICOLOGICO; ASPIRACION; PERSONAL